EFEKTIVITAS PENDEKATAN KETERAMPILAN PROSES PADA PEMBELAJARAN KONSEP BUNYI DI SEKOLAH DASAR - Ahmad Munawir; Nurdin Kaso (Didaktika : Jurnal Kependidikan, 2020)
Learning sound concepts in elementary schools is still difficult for students to understand because they are passive, learning is not yet concrete, and teachers do not use appropriate methods. This research is to explain the effectiveness of the process skills approach in learning sound concepts in elementary school. The study was conducted in a pre experimental village design with the one group pretest-posttest model. The research subjects were students in 161 Pakkodi public elementary schools, totaling 12 people. The research instruments used were tests, observations, and questionnaires. Data were analyzed descriptively with inferential statistical analysis. Student test results show that a very effective process skills approach is used to teach sound concepts because as many as 66% of students successfully scored very high. The results of teacher observation when learning takes place reach good criteria. Student responses related to the process skills approach were very good because as many as 90% gave positive responses. The results showed that an effective process skills approach was used to teach sound concepts in elementary schoolKeywords: process skills approach, sound concepts, elementary school